«Қазақ əдебиеті» пəні бойынша өткізілетін сабақ түрлері - Рүстемова, Ж.А.; Көкеева, Р.Т. (ҚарМУ баспасы, 2010)
Статья посвящается рассмотрению методических и практических вопросов о видах уроков литературы на основании работ ученого-методиста К.Битибаевой. Авторы, опираясь на предложенную ученым классификацию типов и видов уроков, анализируют существующие виды уроков литературы. Классификация видов подтверждается анализиируемым материалом конкретных уроков литературы. Article is devoted to consideration of methodical and practical questions on kinds of lessons of the literature on the basis of works of Kazakhstan’s scientist and methodologist K.Bitibaeva. Authors of article relied on the basis of the classification of types of lessons of literature offered by scientists and kinds of lessons analyze existing kinds of lessons of the literature. Classification of kinds of lessons of the literature is proved by material of concrete lessons of the literature in school.
Keywords: қазақ әдебиеті; қазақ әдебиет пәні; өткізілетін сабақ түрлері; сабақ түрі